On the Question of the Essence of the Peasant Revolution in Ukraine: A New Perspective of Ukrainian Historians - Korinenko, Pavlo (Ukrainian Peasant, 2025)
purpose. The author sets the goal of carrying out a historiographical analysis of the monograph by S. Kornovenko and N. Kovalyova “The Peasant Revolution in Ukraine (1902–1933): Evolution and Variability of Conceptual Approaches in the 20th – at the Beginning of the 21st Century”, and to justify their own vision of the essence of the Peasant Revolution in Ukraine. The scientific novelty of the article lies in the fact that, through historiographical analysis, it expands scholarly knowledge about the essence of the Peasant Revolution in Ukraine, consistently traces the evolution and conceptual approaches of Ukrainian intellectuals–agrarians and agrarian historians, and proposes possible directions for further research into this academic issue. Conclusions. The conducted research provides a historiographical analysis of the scholarly work by well-known Ukrainian agrarian historians, identifies their contribution to the further development of the study of peasantry. Particular attention is paid to their thorough analysis of the evolution and variability of conceptual approaches to the concept of the Peasant Revolution in Ukrainian historiography over more than 100 years. The authors’ rather tolerant attitude towards academic works, memoirs, and diaries of past agrarian intellectuals is highlighted, as well as their recognition of the contribution made by contemporary agrarian historians—primarily the school of Professor A. H. Morozov—to the accumulation of academic knowledge. The reviewed academic work and the conclusions reached by its authors represent another step forward in the development of peasant studies. The author of the review assumes that in future Ukrainian historiography, researchers of the economic, social, political, and military processes in Ukrainian villages from the beginning of the 20th century to the early 1930s, along with the scholarly category “Peasant Revolution,” will continue to use such scholarly categories as “agrarian revolution,” “agrarian policy,” “agrarian transformations,” “revolutionary peasant struggle,” and others.